1958
DOI: 10.1152/ajplegacy.1958.194.1.197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Changes in Intraluminal Pressure on Inotropic and Chronotropic Responses of Isolated Mammalian Hearts

Abstract: The effect of increasing the intraluminal pressure in the right heart on the activity of isolated perfused dog hearts and the effect of increasing the intraluminal pressure on the activity of isolated right atria of dogs, rabbits, guinea pigs and albino rats have been studied. It has been observed that there is a direct relationship between the magnitude of intraluminal right atrial pressure and the inotropic and chronotropic responses of the whole heart and right atrium up to certain critical pressures (5–15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…Intracellular records showed reduced diastolic potential in sinus preparation as well as in Purkinje fibers during stretch. Sjostrand [1964], in agreement with Pathak [1958b] observed stretch acceleration in iso lated atria.…”
Section: Am M Alssupporting
confidence: 74%
See 1 more Smart Citation
“…Intracellular records showed reduced diastolic potential in sinus preparation as well as in Purkinje fibers during stretch. Sjostrand [1964], in agreement with Pathak [1958b] observed stretch acceleration in iso lated atria.…”
Section: Am M Alssupporting
confidence: 74%
“…Change of temperature from 20 to 40 °C and administration of cocaine, procaine, T E A and veratramine in isolated rabbit atrial preparations did not change the pressure-acceleration response significantly. Pathak [1958b] investigated the effect of increased intraluminal pres sure in the right heart upon the activity of isolated dog hearts perfused through the coronary arteries and the effect of distension of the isolated right atrium in dogs, rabbits, guinea pigs and albino rats. He observed a direct relationship between right atrial pressure and both inotropic and chronotropic responses of whole hearts and right atria up to a critical pressure between 5 and 15 mm Hg.…”
Section: Am M Alsmentioning
confidence: 99%
“…A positive chronotropic response has been induced by several mechanisms including mechanical stretch of sinus nodal tissue in isolated perfused hearts (52) or of sinus node (53), atrial pressure increase in isolated denervated hearts (54,55), and perfusion pressure reduction of the sinus nodal artery (56). Similarly, it was shown that the positive chronotropic effect produced by traction on the sinus nodal region or on atrial appendages is purely sympathetically mediated (57,58).…”
Section: Figure 3 Normal Post-ectopic Blood Pressure and R-r Intervalmentioning
confidence: 99%
“…A change in right atrial pressure (RAP) will alter heart rate (HR) through mechanisms that do not use nervous pathways 1–6 . This phenomenon, termed intrinsic cardiac rate regulation (ICRR), may facilitate the adjustment of right heart function to handle fluctuations in venous return.…”
Section: Introductionmentioning
confidence: 99%